Connecting Crabs, Currents, and Coastal Communities: Examining the Impacts of Changing Ocean Conditions on the Distribution of U.S. West Coast Dungeness Crab Commercial Catch - Magel, Caitlin L.; Lee, Elizabeth M. J.; Strawn, Astrea M.; Swieca, Kelsey; Jensen, Andrew D. (Frontiers in Marine Science, 2020)
Dungeness crab (Cancer magister) is one of the most lucrative fisheries on the U.S. west coast. There have been large spatial and temporal fluctuations in catch, which reflect the interconnected influences of the coupled natural-human fishery system. Changing ocean conditions are likely to further alter the magnitude and distribution of Dungeness crab catch, the impacts of which will propagate ecologically and through the social systems of fishing communities. Therefore, the effect of changing ocean conditions on U.S. west coast Dungeness crab catch per unit effort (CPUE) was used as an interdisciplinary case study to examine the susceptibility, a metric that integrates Dungeness crab reliance and social vulnerability indices, of coastal communities to changes in the fishery. Statistical models indicated that ocean conditions influence commercial CPUE three to five years later and that CPUE is likely to decline in the future as ocean conditions change. In particular, sea surface temperature scenarios for 2080 (+1.7 °C and +2.8 °C) reduced Dungeness crab CPUE by 30-100%, depending on fishing port latitude. Declines in Dungeness crab CPUE were greater for southern port communities than for northern port communities under both scenarios – demonstrating greater exposure at the southern end of the species range. We show that U.S. west coast communities are differentially susceptible to a decline in Dungeness crab catch, with Washington communities being at least five times more susceptible than California communities. Our overall assessment showed varying levels of risk (a combination of exposure and susceptibility) for Dungeness crab fishing ports that do not necessarily align with regional or fishery management boundaries.